Online talent platforms, labour market intermediaries and the changing world of work - Lenaerts, Karolien; Kilhoffer, Zachary; de Groen, Willem Pieter; Bosc, Romain; Salez, Nicolas; Eichhorst, Werner; Ody, Margard; Askitas, Nikolaos; Meys, Nicolas (Bonn, 2018)
"By comparing the online talent platform economy and the temporary agency work sector, this study aims to contribute to a rapidly growing literature on new forms of work and their impact on the labour market. It shows that online talent platforms and temporary work agencies do have features in common, but there are also significant differences between the two, which make it difficult to use temporary agency work as a model for the online talent platform economy; in many cases, it would not be a good fit. That being said, the call by policy-makers, social partners and other stakeholders for a level playing field should not be overlooked. Furthermore, the study also confirms that any comparison of the online talent platform economy and the temporary agency work sector is hampered by a lack of data. In order to address this issue, continued monitoring and much more transparency of online talent platforms will be needed, as well as further data collection and analysis of both the online talent platforms and the temporary work agencies. These efforts are important because more flexible forms of work are likely to become increasingly prevalent in the future."